Depression in relation to sex and gender expression among Swedish septuagenarians—Results from the H70 study - Therese Rydberg Sterner; Pia Gudmundsson; Hanna Falk; Nazib Seidu; Felicia Ahlner; Hanna Wetterberg; Lina Rydén; Robert Sigström; Svante Östling; Anna Zettergren; Silke Kern; Margda Waern; et al. (PLoS ONE, 2020)
Objective Little is known about the role of gender expression (femininity, masculinity, or androgyny) in relation to sex differences in depression. This study tested if gender expression was associated with depression and burden of depressive symptoms in a 70-year-old population. Methods A cross-sectional population-based sample of 70-year-olds from The Gothenburg H70 Birth Cohort Study (n = 1203) was examined in 2014–16. Data were collected using psychiatric examinations and structured questionnaires, including the Positive-Negative Sex-Role Inventory to assess gender expression. Depression was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders criteria, and symptom burden was assessed with Montgomery Åsberg Depression Rating Scale (MADRS). Results Gender expression was related to MADRS score and depression diagnosis. In fully adjusted models, feminine traits with low social desirability (FEM-) were associated with a higher MADRS score (R2 0.16; B 0.16; CI 0.1–0.2), while androgyny (t ratio) (R2 0.12; B 0.42; CI 0.1–0.7) and masculine traits with high social desirability (MAS+) (R2 0.13; B -0.06; CI -0.1–-0.01) were associated with a lower MADRS score. Also, feminine traits with low social desirability (FEM-) were positively associated with depression (OR 1.04; CI 1.01–1.1). No associations between depression and masculinity or androgyny were observed in adjusted models. There were no interactions between sex and gender expression in relation to depression or MADRS score, indicating that the effects of gender expression were similar in men and women. Conclusions We found that gender expression was associated to both depression and burden of depressive symptoms. More specifically, we found that femininity was associated to higher levels of depression, irrespective of biological sex. In addition, masculinity and androgyny were associated with lower levels of depression. These results highlight the importance of taking gender expression into consideration when studying sex differences in depression among older populations in future studies.